The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1002/pa.2311
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing India's current account balance: Implication for achieving its external sector sustainability

Abstract: Using annual data for the period 1980-1981 to 2014-2015, the study explores the impact of crude oil imports and real exchange rate on India's current account performance. Utilizing the recent co-integration econometric tools on a current account balance model, the findings contrary to the theoretical prediction revealed that crude oil import significantly improves the current account balance in the long run. Furthermore, the fiscal balance and financial development significantly contribute to the current accou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 81 publications
0
7
0
Order By: Relevance
“…These countries include Malaysia, Indonesia, Vietnam, Philippines, Cambodia, Myanmar, Singapore, and Laos. Following the model by Sadiku et al (2015), Ozdamar (2016), Destaings (2017), Sahoor et al (2022) and Sumiyati (2022), this study delves into the macroeconomic factors influence the current account (CA). Therefore, the estimation model has been formulated as follows: CA𝑖𝑡 = αₒ + β₁ER 𝑖, + β₂MS 𝑖,𝑡 + β₃TOT 𝑖,𝑡 + β₄OILP 𝑖,𝑡 + β₅IR 𝑖,𝑡 + Ԑ…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…These countries include Malaysia, Indonesia, Vietnam, Philippines, Cambodia, Myanmar, Singapore, and Laos. Following the model by Sadiku et al (2015), Ozdamar (2016), Destaings (2017), Sahoor et al (2022) and Sumiyati (2022), this study delves into the macroeconomic factors influence the current account (CA). Therefore, the estimation model has been formulated as follows: CA𝑖𝑡 = αₒ + β₁ER 𝑖, + β₂MS 𝑖,𝑡 + β₃TOT 𝑖,𝑡 + β₄OILP 𝑖,𝑡 + β₅IR 𝑖,𝑡 + Ԑ…”
Section: Methodsmentioning
confidence: 99%
“…When the exchange rate increases or an appreciation of the exchange rate reduces the value of exports and causes a trade balance deficit, it increases or decreases the current account deficit. Empirically, in-depth studies have been done by Astuti, Oktavilia and Rahman (2015), Das (2016), Purwono, Mucha, andMubin (2018), andSahoor et al (2022). These studies showed that the exchange rate negatively influences the current account deficit.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, our study reveals that the substantial rise in deficit of the goods account may be a major contributor to the overall unsustainability of the CAD in India. More precisely, structural reasons such as inelastic demand for oil imports and sectoral constraints may be to blame for India's unsustainable goods account (Rangarajan & Mishra, 2013; Sahoo et al, 2020). As a result, structural reforms targeted at restoring trade competitiveness and improving the export position in the products market will assist India's goods account balance as well as its overall CA situation.…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 99%